Penguatan nilai-nilai iman kristiani melalui optimalisasi lembaga pendidikan agama: Sebuah studi persepsi dan ekspektasi program studi magister Manajemen Pendidikan Kristen melalui survei pada tingkat pendidikan menengah - Betty Arli Sonti Pakpahan; Lasmaria Nami Simanungkalit; Juliber Arman Simanjuntak; Cindy Romauli C. Simanjuntak (KURIOS, 2023)
This research aims to determine students' perceptions and expectations of the Master of Christian Education Management study program. The students in this research were school principals at the SMA/SMK level in Humbang Hasundutan and North Tapanuli Regencies. The survey method is the approach used in this research. The number of respondents in this research was 74 respondents. The results of the research show that the perception of high school/vocational school principals towards the IAKN Tarutung Postgraduate Christian Education Management Masters Study Program, in general, each item is in the good and very good categories. Values are in the intervals 68-83% and 84-100%. Then, the perception of high school/vocational school principals towards the IAKN Tarutung Postgraduate Christian Education Management Masters Study Program, is included in the very good category, in the interval 84-100%. This shows that the perceptions and expectations of students in the Master of Christian Education Management study program are very good and their existence is very much needed